Maternal serum soluble fms-like tyrosine kinase-1-to-placental growth factor ratio distinguishes growth-restricted from non-growth-restricted small-for-gestational-age fetusesAJOG Global Reports at a Glance - Prithi Rajiv, MD; Thomas Cade, MD; Jennifer Dean, MD; Gabriel Davis Jones, MD; Shaun P. Brennecke, MD, PhD (Elsevier, 2024)
BACKGROUND: Fetal growth restriction secondary to chronic placental insufficiency is a major cause of perinatal morbidity and mortality. A significant proportion of fetuses with fetal growth restriction are small for gestational age, defined as a birthweight of ≤10th percentile. However, not all small-for-gestational-age fetuses are growth restricted. Some are constitutionally small and otherwise healthy. It is important to distinguish between small-for-gestational-age fetuses with and without fetal growth restriction to ensure appropriate interventions in small-for-gestational-age fetuses with fetal growth restriction and to minimize unnecessary interventions in healthy small-for-gestational-age fetuses. The maternal serum ratio of soluble fms-like tyrosine kinase-1 and placental growth factor is an indicator of placental insufficiency in the latter half of pregnancy. As such, the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio may be a clinically useful tool to distinguish between small-for-gestational-age fetuses with and without fetal growth restriction. OBJECTIVE: This study aimed to determine whether the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio can distinguish between small-for-gestational-age fetuses with and without fetal growth restriction with a birthweight of ≤10th percentile. STUDY DESIGN: A retrospective audit of 233 singleton pregnancies delivering an infant with a birthweight of ≤10th percentile corrected for gestational age with an antenatal maternal serum soluble fms-like tyrosine kinase-1-to-placental growth factor result was performed. Fetal growth restriction was defined as a birthweight of ≤10th percentile with an umbilical artery pulsatility index of >95th percentile, fetal middle cerebral artery pulsatility index of <5th percentile, amniotic fluid index of <6 cm, and/or cerebroplacental ratio of <1st percentile. The soluble fms-like tyrosine kinase-1-to-placental growth factor ratios before delivery between fetuses with and without fetal growth restriction (121 [fetal growth restriction] vs 112 [no fetal growth restriction]) were compared. The Student t test and Fisher exact test were used to compare cases and controls. The Mann-Whitney U test, linear regression analysis, and Spearman correlation coefficient (Rho) were used to examine associations between the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio and fetal outcomes to determine whether the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio served as a prognostic marker of fetal growth restriction severity. RESULTS: The mean soluble fms-like tyrosine kinase-1-to-placental growth factor ratio was increased in fetal growth restriction cases compared with non-fetal growth restriction controls (234.3±25.0 vs 67.4±7.7, respectively; P<.0001). When controlling for preeclampsia, which is associated with placental insufficiency, fetal growth restriction cases still demonstrated an independent increase in the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio (effect size, 0.865; 95% confidence interval, 0.509-1.220; P<.001). The soluble fms-like tyrosine kinase-1-to-placental growth factor ratio was negatively correlated with birthweight percentiles in pregnancies delivering an infant with a birthweight of ≤10th percentile (r=−0.3565; P<.0001). This association was maintained for fetuses with fetal growth restriction (r=−0.2309; P<.05), whereas fetuses without fetal growth restriction had no significant correlation between the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio and neonatal birthweight percentiles. CONCLUSION: The soluble fms-like tyrosine kinase-1-to-placental growth factor ratio was significantly higher in small-for-gestational-age fetuses with fetal growth restriction than small-for-gestational-age fetuses without fetal growth restriction, independent of preeclampsia. Furthermore, the soluble fms-like tyrosine kinase-1-to-placental growth factor ratio was negatively correlated with fetal growth restriction birthweight percentiles, suggesting that it may be a clinical measure of fetal growth restriction severity. Therefore, the ratio may usefully delineate fetal growth restriction from constitutionally small but otherwise healthy fetuses antenatally, allowing for timely interventions in small-for-gestational-age cases with fetal growth restriction and unnecessary interventions to be minimized in small-for-gestational-age cases without fetal growth restriction.